Attention‐Induced Trading and Returns: Evidence from Robinhood Users - BARBER, BRAD M.; HUANG, XING; ODEAN, TERRANCE; SCHWARZ, CHRISTOPHER (Journal of Finance, 2022)
ABSTRACT We study the influence of financial innovation by fintech brokerages on individual investors’ trading and stock prices. Using data from Robinhood, we find that Robinhood investors engage in more attention‐induced trading than other retail investors. For example, Robinhood outages disproportionately reduce trading in high‐attention stocks. While this evidence is consistent with Robinhood attracting relatively inexperienced investors, we show that it is also driven in part by the app's unique features. Consistent with models of attention‐induced trading, intense buying by Robinhood users forecasts negative returns. Average 20‐day abnormal returns are −4.7% for the top stocks purchased each day.